Enhanced Photoluminescence in Quantum Dots–Porous Polymer Hybrid Films Fabricated by Microcellular Foaming. Issue 12 (24th April 2019) - Yu, Shudong; Fritz, Benjamin; Johnsen, Siegbert; Busko, Dmitry; Richards, Bryce S.; Hippler, Marc; Wiegand, Gabriele; Tang, Yong; Li, Zongtao; Lemmer, Uli; Hölscher, Hendrik; Gomard, Guillaume
Abstract: The color conversion efficiency of thin polymeric layers embedding quantum dots (QDs) is limited by their negligible light scattering ability and by the insufficient absorption of the excitation photons. In this study, a route is presented to tackle these optical shortcomings by introducing a tailored network of micropores inside these hybrid films. This is achieved by exploiting the microcellular foaming approach which is rapid, cost effective and only makes use of a green solvent (supercritical carbon dioxide). With an appropriate combination of the applied pressure and temperature during foaming, and by using a proper film thickness, the photoluminescence (PL) intensity is enhanced by a factor of up to 6.6 compared to an equivalent but unfoamed hybrid film made of CdSe/ZnS QDs in a polymethyl methacrylate matrix. Spectroscopic measurements and ray tracing simulations reveal how the porous network assists UV/blue light absorption by the QDs and the subsequent outcoupling of the converted light. The approach improves the PL for various QD concentrations and can be easily scaled up and extended to other polymeric matrices as well as light converting materials. Abstract : Porous polymer films embedded with quantum dots are fabricated by microcellular foaming to boost their light conversion efficiency. A significant photoluminescence enhancement is achieved via the controlled incorporation of a micro‐porous network, which elongates the average optical path length of the exciting light in the converting medium and assists the extraction of the downshifted photons from the hybrid films.